2016
DOI: 10.1177/0969733016638143
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ethical climate types on nurses’ behaviors in Bosnia and Herzegovina

Abstract: Public and private hospitals can enhance overall job satisfaction and organizational commitment by altering the ethical climate of organizations. Hospital administrations should nurture caring and rule types of ethical climate which influence overall satisfaction. By this way, they could reduce nursing shortage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 39 publications
3
35
0
4
Order By: Relevance
“…The impact of caring climate is both direct and indirect. This result is consistent with a previous literature (Fu & Deshpande, 2013;Dinc & Huric, 2016). The employees who believed that their banks had a caring climate were overally more satisfied with their job, affectively committed to their organization, and had better job performance.…”
Section: Conclusion and Limitationssupporting
confidence: 92%
See 2 more Smart Citations
“…The impact of caring climate is both direct and indirect. This result is consistent with a previous literature (Fu & Deshpande, 2013;Dinc & Huric, 2016). The employees who believed that their banks had a caring climate were overally more satisfied with their job, affectively committed to their organization, and had better job performance.…”
Section: Conclusion and Limitationssupporting
confidence: 92%
“…For example, Deshpande's (1996) Okpara and Wynn (2008) also found that in Nigerian context caring climate had a significant positive influence on overall JS. Additionally, Dinc and Huric (2016) have shown that "caring" and "rules" climate types have a significant and positive effect on overall JS in a survey of 171 nurses of public and private hospitals in BiH. This research expects that caring climate will significantly impact overall JS of employees of public and private banks and thus proposes the following hypothesis:…”
Section: Caring Climatementioning
confidence: 88%
See 1 more Smart Citation
“…This result complies with the findings of the literature (Tsai and Huang, 2008;Dinc and Huric, 2016). Caring climate is expected to be higher than law and code climate.…”
Section: Discussionsupporting
confidence: 92%
“…Despite all these improvements, BiH's development is very slow and it is still in a transition period. General perception for the reason of this slow improvement is the central government with a rotating, tripartite presidency and its heavy bureaucracy (Dinc and Huric, 2016). Therefore, people, especially the youth in BiH, has a prejudice and do not see their future in this country.…”
Section: Discussionmentioning
confidence: 99%